Forest Income as an Insurance Diversification Strategy among Rural Farmers in South Nandi, Kenya - Sumukwo , Joel (African Journal of Education,Science and Technology (AJEST), 2017)
Limited income opportunities and lack of formal insurance schemes among farmers in sub-Sahara Africa have impeded rural economic development. This paper examines the insurance diversification function of forest income among households in South Nandi of Kenya. Using survey data of 224 households located within a 4 km radius of South Nandi forest, income diversification strategies and insurance role of forest products are examined. Results show that forest incomes contribute significantly (24%) to total household income. Diversification model indicates that farm income has an inverse effect on level of diversification. That is, increased farm income reduces income diversification strategies among the households. The residents consider improved farm income stream promotes financial security and stability. But the off-farm income is not associated with reduced diversification of household income sources among residents of South Nandi. Results show that forest income has a positive and significant effect on the index of diversification forest income. Hence forest income is an important natural insurance diversification strategy to rural households as it assumes an option value to over half of the residents. This study suggests that to reduce consumption and income shocks, programs that coevally enhance agricultural efficiency and reliability of forest income should be adopted. In conclusion, the stated insurance premium value above (40%) maximum willingness to pay would guarantee the continued flow of forest services in the future irrespective of whether there is current consumption or not. Further, the benefits from forest income diversification in risk management should be integrated in forest conservation policies.